Secondary battery, method for manufacturing the same, and electric device

CN122800683APending Publication Date: 2026-09-22CONTEMPORARY AMPEREX TECHNOLOGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510336090.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-20
Publication Date
2026-09-22

Smart Images

  • Figure CN122800683A_ABST
    Figure CN122800683A_ABST
Patent Text Reader

Abstract

This application provides a secondary battery and its preparation method and electrical device. The secondary battery includes a positive electrode sheet, which includes a positive current collector and a positive electrode film layer located on at least one side of the current collector. The positive electrode film layer includes a positive active material, a first binder, and a second binder. The first binder comprises primary particles, and the second binder is fibrous. The particle size of the positive active material is greater than or equal to the particle size of the primary particles of the first binder, and the particle size of the positive active material is 0.5 μm to 10 μm. The primary particles of the first binder are distributed on at least a portion of the surface of the positive active material. The secondary battery provided by this application combines excellent storage performance with low internal resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, and in particular to a secondary battery, its preparation method, and an electrical device thereof. Background Technology

[0002] In recent years, with the increasingly wide application of rechargeable batteries, they have been widely used in energy storage power systems such as hydropower, thermal power, wind power, and solar power plants, as well as in power tools, electric bicycles, electric motorcycles, electric cars, aerospace, and many other fields. With the application and promotion of rechargeable batteries, people have increasingly higher requirements for their internal resistance and storage performance.

[0003] Therefore, how to achieve both excellent storage performance and low internal resistance in secondary batteries has become an urgent technical problem to be solved. Summary of the Invention

[0004] This application is made in view of the above-mentioned problems, and its purpose is to provide a secondary battery and a method for preparing the same, as well as an electrical device thereof. The secondary battery prepared in this application can achieve both excellent storage performance and low internal resistance.

[0005] To achieve the above objectives, a first aspect of this application provides a secondary battery, including a positive electrode sheet, the positive electrode sheet including a positive current collector and a positive electrode film layer located on at least one side of the positive current collector, the positive electrode film layer including a positive electrode active material, a first binder and a second binder, the first binder including primary particles, the second binder being fibrous, the particle size of the positive electrode active material being greater than or equal to the particle size of the primary particles of the first binder, the particle size of the positive electrode active material being 0.5 μm to 10 μm, and the primary particles of the first binder being distributed on at least a portion of the surface of the positive electrode active material.

[0006] In this application, the particle size of the positive electrode active material is 0.5 μm to 10 μm. Smaller particle sizes shorten the diffusion distance of ions and increase the ion transport rate, which is beneficial for improving the rate performance of the secondary battery. The particle size of the positive electrode active material is greater than or equal to the particle size of the primary particles of the first binder, allowing the primary particles of the first binder to be distributed on at least a portion of the surface of the small-particle-size positive electrode active material. This enables the primary particles of the first binder to establish short-range bonding paths between adjacent positive electrode active material particles. Simultaneously, the second binder is fibrous, and the fibers can interweave to form a network structure that wraps around the surfaces of the primary particles of the positive electrode active material and the first binder. This allows the second binder to establish long-range bonding paths between distant positive electrode active materials, between the first binders, and between the positive electrode active material and the first binder, thereby improving the bonding effect of the positive electrode sheet and thus enhancing the storage performance of the secondary battery. Furthermore, the distribution of the primary particles of the first binder on the surface of the small-diameter positive electrode active material allows for relatively uniform and close contact between the primary particles and the positive electrode active material particles. This forms a relatively continuous and uniform conductive network within the positive electrode sheet, enabling efficient electron transport and reducing the film resistance of the positive electrode sheet, thus improving the internal resistance of the secondary battery. Therefore, the secondary battery of this application can achieve both excellent storage performance and low internal resistance.

[0007] In some embodiments, the particle size of the positive electrode active material is 0.5 μm to 5 μm, and / or the particle size of the primary particles of the first binder is 0.1 μm to 0.5 μm. This facilitates the distribution of the primary particles of the first binder on the surface of the small-particle-size positive electrode active material, which on the one hand improves the bonding effect of the positive electrode sheet, and on the other hand reduces the film resistance of the positive electrode sheet, thereby helping the secondary battery to achieve both excellent storage performance and low internal resistance.

[0008] In some embodiments, the particle size of the positive electrode active material is 1 μm to 4 μm, and / or the particle size of the primary particles of the first binder is 0.15 μm to 0.2 μm. This further improves the bonding effect of the positive electrode sheet and further reduces the film resistance of the positive electrode sheet, thus making it more advantageous for the secondary battery to achieve both excellent storage performance and low internal resistance.

[0009] In some embodiments, the mass ratio of the first binder to the second binder in the positive electrode film layer is (1-15):1. This improves electron transport efficiency and overall conductivity of the positive electrode sheet without affecting the bonding effect, thereby further reducing the film resistance of the positive electrode sheet. This allows the secondary battery to achieve both excellent storage performance and low internal resistance.

[0010] In some embodiments, the mass ratio of the first binder to the second binder in the positive electrode film layer is (2-8):1. This allows for further reduction of the film resistance of the positive electrode sheet without affecting the bonding effect, making it easier for the secondary battery to achieve both excellent storage performance and low internal resistance.

[0011] In some embodiments, the second binder includes a fiberizable binder. Therefore, the second binder can improve the bonding effect of the positive electrode sheet, thereby improving the storage performance of the secondary battery.

[0012] In some embodiments, the first binder comprises polyvinylidene fluoride and / or polyvinylidene fluoride-hexafluoropropylene copolymer. Thus, the aforementioned first binder can improve the bonding effect of the positive electrode sheet and reduce the film resistance of the positive electrode sheet, thereby helping the secondary battery to achieve both excellent storage performance and low internal resistance.

[0013] In some embodiments, the number average molecular weight of the first adhesive is 200,000 to 2,000,000. This is beneficial for increasing the strength of the first adhesive, thereby improving the bonding effect.

[0014] In some embodiments, the positive electrode film layer further includes a conductive agent, the particle size of which is smaller than the particle size of the primary particles of the first binder. This improves the conductivity of the positive electrode, thereby enabling the secondary battery to achieve both excellent storage performance and low internal resistance.

[0015] In some embodiments, the particle size of the conductive agent is 5 nm to 50 nm. This allows the conductive agent to be distributed on the primary particles of the first binder and the surface of the positive electrode active material, thereby improving the conductivity of the positive electrode sheet and consequently enabling the secondary battery to achieve both excellent storage performance and low internal resistance.

[0016] In some implementations, the secondary battery includes one or more of the following features:

[0017] (1) In the positive electrode film layer, the mass percentage of the positive electrode active material is 90% to 99%; (2) In the positive electrode film layer, the mass percentage of the first binder is 0.5% to 6%; (3) In the positive electrode film layer, the mass percentage of the second binder is 0.1% to 6%; (4) In the positive electrode film layer, the mass percentage of the conductive agent is 0.4% to 4%.

[0018] In some embodiments, the positive electrode active material includes one or more of lithium-containing transition metal oxides, lithium-containing phosphates, and their respective modified compounds.

[0019] In some implementations, the positive electrode active material includes lithium iron phosphate.

[0020] In some embodiments, the shear strength of the positive electrode sheet is 0.6 MPa to 1.2 MPa. This indicates that the positive electrode sheet has a good bonding effect, which is beneficial to improving the storage performance of the secondary battery.

[0021] In some embodiments, the film resistance of the positive electrode is 0.01Ω to 0.2Ω. This reflects that the positive electrode has a low impedance, which is beneficial for reducing the internal resistance of the secondary battery.

[0022] The second aspect of this application provides a method for preparing a secondary battery, used to prepare the secondary battery described in the first aspect. The method for preparing the secondary battery includes a positive electrode preparation step, which includes a mixing step, comprising pulverizing a first binder raw material, wherein the median particle size of the pulverized first binder raw material is 1 μm to 2 μm, and then stirring the positive electrode active material, the pulverized first binder raw material, and the second binder raw material under stirring conditions of a stirring linear velocity of 5 m / s to 20 m / s and a stirring temperature of -20℃ to 40℃ to obtain a dry-mixed powder containing a positive electrode active material, a first binder, and a second binder raw material. A binder comprises primary particles, wherein the particle size of the positive electrode active material is greater than or equal to the particle size of the primary particles of the first binder, and the particle size of the positive electrode active material is 0.5 μm to 10 μm; a fiberization step includes fiberizing the dry-mixed powder to obtain a fiberized mixed powder containing the positive electrode active material, the first binder, and the second binder, wherein the second binder is fibrous; a tableting step includes calendering the fiberized mixed powder to obtain an electrode film, and then rolling the electrode film with the positive electrode current collector at room temperature to obtain a positive electrode sheet.

[0023] In this application, by pulverizing, the median particle size of the first binder raw material can be reduced to the aforementioned range. Then, under the aforementioned conditions, stirring is performed to disperse the first binder raw material from secondary particles into primary particles with a particle size less than or equal to that of the positive electrode active material. In this way, the primary particles of the first binder can be distributed on the surface of the small-diameter positive electrode active material. On the one hand, this facilitates the establishment of short-range bonding paths between adjacent positive electrode active material particles by the primary particles of the first binder. On the other hand, this distribution method allows the primary particles of the first binder to contact the positive electrode active material particles relatively uniformly and tightly, thereby forming a relatively continuous and uniform conductive network inside the positive electrode sheet. This allows for efficient electron transport, which helps to reduce the film resistance of the positive electrode sheet. Consequently, the secondary battery can achieve both excellent storage performance and low internal resistance. Meanwhile, the fiberization process enables the second binder raw material to form a fibrous second binder. The fibers can interweave to form a network structure that wraps around the surface of the primary particles of the positive electrode active material and the first binder. In this way, the second binder can establish long-range bonding paths between the positive electrode active materials that are far apart, between the first binders, and between the positive electrode active material and the first binder. This is more conducive to improving the bonding effect of the positive electrode sheet, and thus can further improve the storage performance of the secondary battery.

[0024] Furthermore, since the two binders have the aforementioned positional distribution relationship and are relatively uniformly distributed in the positive electrode film layer, heating is not required during the preparation process, especially during calendering and roll forming processes, to achieve a good bonding effect between the two binders, which helps to reduce energy consumption.

[0025] In some embodiments, the fiberization process includes one or more of high-speed shearing, air jet milling, and screw extrusion. Using these methods allows the second binder raw material to be fiberized into fibers without heating, which helps to further reduce energy consumption.

[0026] In some embodiments, the high-speed shearing process is carried out at a shearing rate of 30 m / s to 50 m / s for 5 min to 30 min. Under these conditions, the high-speed shearing process can utilize the frictional heat generated between the dry-mixed powders during the shearing operation to promote the fiberization of the second binder raw material. Therefore, this application can achieve the fiberization process without an additional heating source, which is beneficial for further reducing energy consumption.

[0027] In some embodiments, the preparation method includes one or more of the following features:

[0028] (1) The calendering pressure is 1t to 10t, which is beneficial for obtaining the electrode film; (2) The rolling composite treatment pressure is 1t to 20t, which makes the first binder plasticized and softened, thereby enabling the positive electrode active material particles to be bonded together and the electrode film to be combined with the positive electrode current collector; (3) The stirring time of the stirring treatment is 30min to 180min, which is beneficial for dispersing the pulverized first binder raw material from secondary particles into primary particles with a particle size of 0.1μm to 0.5μm; (4) The median particle size of the second binder raw material is 100μm to 600μm. Therefore, it is beneficial for the second binder material to be fibrous with a suitable diameter after fiberization treatment; (5) the median particle size of the first binder material is 1μm to 10μm, which is beneficial for the first binder material to be dispersed into primary particles with a particle size of 0.1μm to 0.5μm after crushing and stirring treatment; (6) the mass ratio of the crushed first binder material and the second binder material is (1 to 15):1, which can further reduce the film resistance of the positive electrode without affecting the bonding effect, that is, it is more beneficial for the secondary battery to have both excellent storage performance and low internal resistance.

[0029] In some embodiments, the dry-mixed powder also includes a conductive agent during the mixing step. This conductive agent further improves the conductivity of the positive electrode, thus helping the secondary battery to achieve both excellent storage performance and low internal resistance.

[0030] In some embodiments, the mass ratio of the positive electrode active material, the pulverized first binder raw material, the second binder raw material, and the conductive agent is (90–99):(0.5–6):(0.1–6):(0.4–4). This allows the secondary battery to achieve both excellent storage performance and low internal resistance.

[0031] A third aspect of this application provides an electrical device, which includes the secondary battery described in the first aspect, or a secondary battery prepared according to the preparation method described in the second aspect. Attached Figure Description

[0032] Figure 1 This is a schematic diagram of the structure of the positive electrode film layer according to one embodiment of this application.

[0033] Figure 2 This is a schematic diagram of a battery cell according to one embodiment of this application.

[0034] Figure 3 yes Figure 2 An exploded view of a battery cell according to one embodiment of this application is shown.

[0035] Figure 4 This is a schematic diagram of a battery module according to one embodiment of this application.

[0036] Figure 5 This is a schematic diagram of a battery pack according to one embodiment of this application.

[0037] Figure 6 yes Figure 5 An exploded view of a battery pack according to one embodiment of this application is shown.

[0038] Figure 7 This is a schematic diagram of a battery device used as a power source according to an embodiment of this application.

[0039] Figure 8 This is a scanning electron microscope image of the positive electrode in Embodiment 1 of this application.

[0040] Figure 9 yes Figure 8 A partially enlarged scanning electron microscope image of the positive electrode in Embodiment 1 of this application is shown.

[0041] Explanation of reference numerals in the attached figures:

[0042] 10 Positive electrode film layer; 101 Positive electrode active material; 102 First binder; 103 Second binder; 104 Conductive agent; 1 Battery pack; 2 First housing; 3 Second housing; 4 Battery module; 5 Battery cell; 51 Housing; 52 Electrode assembly; 53 Top cover assembly. Detailed Implementation

[0043] The following detailed description, with appropriate reference to the accompanying drawings, discloses the secondary battery, its preparation method, and embodiments of the power-using device of this application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided for the purpose of enabling those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.

[0044] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0045] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0046] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0047] Unless otherwise specified, all steps of this application may be performed sequentially or randomly, preferably sequentially. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, if the method may also include step (c), it means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0048] Unless otherwise specified, the terms used in this application have the common meanings as commonly understood by those skilled in the art.

[0049] Unless otherwise specified, the values ​​of the parameters mentioned in this application can be determined using various testing methods commonly used in the art, for example, according to the testing methods given in this application.

[0050] Currently, the manufacturing of electrodes for secondary batteries mainly employs a wet coating process, where a slurry is coated onto the surface of the current collector and then baked at high temperatures to remove the solvent. However, high-temperature drying cannot completely remove the solvent, leaving residual solvent in the electrode that can further affect the storage performance of the secondary battery. Furthermore, for toxic solvents, such as N-methylpyrrolidone (NMP), solvent recovery is required, which increases the complexity of the process and raises the manufacturing cost of the electrode. Additionally, wet electrode technology limits the thickness and coating weight of the electrode, thus affecting the energy density of the secondary battery.

[0051] In related technologies, the use of solvent-free dry electrode technology to replace traditional wet electrode technology not only eliminates solvent residue and improves the storage performance of secondary batteries, but also saves manufacturing costs and is more environmentally friendly. Furthermore, dry electrode technology can increase electrode thickness and compaction density, resulting in higher energy density in secondary batteries. However, current dry electrode technologies suffer from uneven binder distribution, failing to provide sufficient adhesion. To improve adhesion, the amount of binder is typically increased, but this increases hinder electron conduction between active material particles, negatively impacting the electrode's film resistance. Therefore, current dry electrode technologies, in order to ensure electrode adhesion, result in relatively high internal resistance in the prepared electrodes, meaning that secondary batteries cannot simultaneously achieve high storage performance and low internal resistance.

[0052] Based on this, this application proposes a secondary battery, a method for preparing the same, and an electrical device thereof. The secondary battery prepared in this application can achieve both excellent storage performance and low internal resistance. The following provides a more detailed description of this application and its optional embodiments.

[0053] Secondary batteries

[0054] The first aspect of this application provides a secondary battery, including a positive electrode sheet, the positive electrode sheet including a positive current collector and a positive electrode film layer located on at least one side of the positive current collector, such as... Figure 1 As shown, the positive electrode film layer 10 includes a positive electrode active material 101, a first binder 102, and a second binder 103. The first binder 102 includes primary particles, and the second binder 103 is fibrous. The particle size of the positive electrode active material 101 is greater than or equal to the particle size of the primary particles of the first binder 102. The particle size of the positive electrode active material is 0.5 μm to 10 μm. The primary particles of the first binder 102 are distributed on at least a portion of the surface of the positive electrode active material 101.

[0055] In this application, the particle size of the positive electrode active material is 0.5 μm to 10 μm. Smaller particle sizes shorten the diffusion distance of ions and increase the ion transport rate, which is beneficial for improving the rate performance of the secondary battery. The particle size of the positive electrode active material is greater than or equal to the particle size of the primary particles of the first binder, allowing the primary particles of the first binder to be distributed on at least a portion of the surface of the small-sized positive electrode active material. This enables the primary particles of the first binder to establish short-range bonding paths between adjacent positive electrode active material particles. Simultaneously, the second binder is fibrous, and the fibers can interweave to form a network structure that wraps around the surfaces of the primary particles of the positive electrode active material and the first binder. This allows the second binder to establish long-range bonding paths between distant positive electrode active materials, between the first binders, and between the positive electrode active material and the first binder, thereby improving the bonding effect of the positive electrode sheet and thus improving the storage performance of the secondary battery. Furthermore, the distribution of the primary particles of the first binder on the surface of the small-diameter positive electrode active material allows for relatively uniform and close contact between the primary particles and the positive electrode active material particles. This forms a relatively continuous and uniform conductive network within the positive electrode sheet, enabling efficient electron transport and reducing the film resistance of the positive electrode sheet, thus improving the internal resistance of the secondary battery. Therefore, the secondary battery of this application can achieve both excellent storage performance and low internal resistance.

[0056] For example, the particle size of the positive electrode active material is 0.5μm~1μm, 0.5μm~2μm, 0.5μm~4μm, 0.5μm~5μm, 0.5μm~6μm, 0.5μm~8μm, 0.5μm~10μm, 1μm~2μm, 1μm~4μm, 1μm~5μm, 1μm~6μm, 1μm~8μm, 1μm~10μm, 2μm~ Values ​​between the ranges of 4μm, 2μm~5μm, 2μm~6μm, 2μm~8μm, 2μm~10μm, 4μm~5μm, 4μm~6μm, 4μm~8μm, 4μm~10μm, 5μm~6μm, 5μm~8μm, 5μm~10μm, 6μm~8μm, 6μm~10μm, 8μm~10μm, or any two of these ranges.

[0057] In this application, the particle size of the positive electrode active material can be either the particle size of the primary particles of the positive electrode active material or the particle size of the secondary particles of the positive electrode active material.

[0058] In some embodiments, the particle size of the positive electrode active material is 0.5 μm to 5 μm, and / or the particle size of the primary particles of the first binder is 0.1 μm to 0.5 μm. Optionally, the particle size of the positive electrode active material is 1 μm to 4 μm, and / or the particle size of the primary particles of the first binder is 0.15 μm to 0.2 μm. This makes it more advantageous for the primary particles of the first binder to be distributed on the surface of the small-particle-size positive electrode active material. On the one hand, it enables the establishment of short-range bonding paths between adjacent positive electrode active material particles, which is more conducive to improving the bonding effect of the positive electrode sheet. On the other hand, it enables the formation of a relatively continuous and uniform conductive network inside the positive electrode sheet, allowing electrons to be transported efficiently, thereby further reducing the film resistance of the positive electrode sheet. This, in turn, is more conducive to the secondary battery achieving both excellent storage performance and low internal resistance. For example, the particle size of the primary particles of the first adhesive is a value within a range of 0.1 μm to 0.15 μm, 0.1 μm to 0.2 μm, 0.1 μm to 0.3 μm, 0.1 μm to 0.4 μm, 0.1 μm to 0.5 μm, 0.15 μm to 0.2 μm, 0.15 μm to 0.3 μm, 0.15 μm to 0.4 μm, 0.15 μm to 0.5 μm, 0.2 μm to 0.3 μm, 0.2 μm to 0.4 μm, 0.2 μm to 0.5 μm, 0.3 μm to 0.4 μm, 0.3 μm to 0.5 μm, 0.4 μm to 0.5 μm, or any combination thereof.

[0059] In this application, the term "particle size" refers to the longest diameter of a material, that is, the distance between the two farthest points on a material particle is taken as the particle size of the material.

[0060] In this application, the term "primary particle" refers to a particle with a complete boundary in the field of view of the positive electrode film under a certain magnification of a scanning electron microscope, such as 10,000x. The particle may contain pores or defects, but there is no complete boundary inside the particle that is sufficient to divide it into two or more particles.

[0061] In this application, the particle size of the material can be measured using a scanning electron microscope (e.g., ZEISS Sigma 300). Specifically: the positive electrode film layer is peeled off from the positive electrode current collector, the peeled-off positive electrode film layer is fixed on the sample stage, the sample stage is installed in the sample holder and locked in place, the power of the argon ion cross-section polisher (e.g., JEOL IB-09010CP argon ion cross-section polisher) is turned on and a vacuum is applied (e.g., 10...). -7The argon flow rate (e.g., 0.12 MPa) and polishing time (e.g., 90 min) are set, and the sample stage is adjusted to swing mode to begin polishing. Polishing is performed at different angles to obtain cross-sections of the positive electrode film at different angles. Scanning electron microscopy is used to observe the cross-sections at different angles. A test sample with a length × width = 50 mm × 100 mm is randomly selected from each cross-section. Multiple test areas (e.g., 5) are randomly selected from the test sample, and the particle size of the positive electrode active material particles and the primary particles of the first binder in each test area is read at a certain magnification (e.g., the distance between the two farthest points on the particle is taken as the particle size of the test material particle). The particle size range of the test particles at that angle is obtained. The particle size of the test particles at different angles is then tested again to obtain the particle size range of the test particles. To ensure the accuracy of the test results, multiple test samples (e.g., 10) can be taken from each cross-section and the above test can be repeated.

[0062] In some embodiments, the mass ratio of the first binder to the second binder in the positive electrode film layer is (1-15):1, optionally (2-8):1. Thus, the contents of both the first and second binders in the positive electrode film layer are within a suitable range. This improves electron transport efficiency and overall conductivity of the positive electrode sheet without affecting the bonding effect, thereby further reducing the film resistance of the positive electrode sheet. This makes it more advantageous for the secondary battery to achieve both excellent storage performance and low internal resistance. For example, the mass ratio of the first binder to the second binder in the positive electrode film layer is a value within a range of 1:1, 2:1, 4:1, 6:1, 8:1, 10:1, 12:1, 15:1, or any combination thereof.

[0063] In this application, the mass ratio of the first binder and the second binder in the positive electrode film layer can be determined using a nuclear magnetic resonance (NMR) spectrometer. Specifically, positive electrode film layer powder is scraped, dissolved in a suitable solvent, and the dissolved sample is placed in an NMR spectrometer for testing to obtain a carbon NMR spectrum. Based on the carbon NMR spectrum, the characteristic peaks of the first and second binders are identified, and the masses of the first and second binders in the positive electrode film layer, as well as the mass ratio of the first binder to the second binder, are calculated using the peak area or peak height.

[0064] In some embodiments, the second binder includes a fibrous binder. Thus, the second binder can be fibrous, which facilitates the establishment of long-range bonding paths between widely spaced positive electrode active materials, between the first binders, and between the positive electrode active materials and the first binder, thereby improving the bonding effect of the positive electrode sheet and consequently enhancing the storage performance of the secondary battery.

[0065] In some embodiments, the second binder includes one or more of polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene copolymer, fluorinated ethylene-propylene copolymer, and tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer. Optionally, the second binder includes PTFE. The aforementioned second binder can be fibrous, which facilitates the establishment of long-range bonding paths between widely spaced positive electrode active materials, between the first binders, and between the positive electrode active material and the first binder, thereby improving the bonding effect of the positive electrode sheet and thus enhancing the storage performance of the secondary battery.

[0066] In some embodiments, the diameter of the fibers in the second binder is 10 nm to 1000 nm, optionally 10 nm to 100 nm. This facilitates the establishment of effective long-range bonding paths between the widely spaced positive electrode active materials, between the first binders, and between the positive electrode active materials and the first binder, thereby improving the bonding effect of the positive electrode sheet and consequently enhancing the storage performance of the secondary battery. Exemplarily, the diameter of the fibers in the second binder is a value within a range of 10 nm, 50 nm, 100 nm, 200 nm, 500 nm, 800 nm, 1000 nm, or any combination thereof.

[0067] In some embodiments, the first binder comprises polyvinylidene fluoride and / or polyvinylidene fluoride-hexafluoropropylene copolymer; optionally, the first binder comprises polyvinylidene fluoride. Thus, the aforementioned first binder can establish short-range bonding paths between adjacent positive electrode active material particles and can form a relatively continuous and uniform conductive network within the positive electrode sheet, thereby improving the bonding effect of the positive electrode sheet and reducing the film resistance of the positive electrode sheet. This, in turn, helps the secondary battery to achieve both excellent storage performance and low internal resistance.

[0068] In some embodiments, the first adhesive may also include one or more of polymethyl methacrylate, polyacrylic acid, polyimide, and sodium carboxymethyl cellulose.

[0069] In some embodiments, the number-average molecular weight of the first adhesive is between 200,000 and 2,000,000, optionally between 600,000 and 1,000,000. A number-average molecular weight within this range is beneficial for increasing the strength of the first adhesive, thereby improving the bonding effect. Exemplarily, the number-average molecular weight of the first adhesive is a value within the range of 200,000, 400,000, 600,000, 800,000, 1,000,000, 1,200,000, 1,500,000, 1,800,000, 2,000,000, or any combination thereof.

[0070] In this application, the number-average molecular weight of the first binder has a meaning known in the art and can be determined using instruments and methods known in the art. For example, it can be determined by gel permeation chromatography according to standard GB / T21863-2008. Specifically, a Waters 2695 Isocratic HPLC gel permeation chromatograph (differential refractive index detector 2141) is used, with a 3.0% polystyrene solution sample as a reference, and a matched column (oil-based: Styragel HT5DMF7.8×300mm + Styragel HT4) is selected. A 3.0% solution of the first binder is prepared using purified N-methylpyrrolidone (NMP) solvent, and the prepared solution is allowed to stand for one day for later use. During testing, tetrahydrofuran is first drawn into a syringe for rinsing, and this is repeated several times. Then, 5 mL of the experimental solution is drawn, the air in the syringe is expelled, the needle tip is dried, and finally the sample solution is slowly injected into the injection port. After the reading stabilizes, the data is obtained, and the number-average molecular weight data is read.

[0071] In some implementations, continue as Figure 1 As shown, the positive electrode film layer 10 also includes a conductive agent 104, the particle size of which is smaller than the particle size of the primary particles of the first binder 102. Adding a conductive agent with a particle size smaller than the primary particles of the first binder to the positive electrode film layer helps to distribute the conductive agent on the surface of both the primary particles of the first binder and the positive electrode active material, thereby improving the conductivity of the positive electrode sheet. This, in turn, helps the secondary battery to achieve both excellent storage performance and low internal resistance.

[0072] In some embodiments, the conductive agent includes conductive carbon particles. Optionally, the conductive agent includes one or more of conductive carbon black, carbon nanotubes, graphene, acetylene black, and Ketjen black.

[0073] In some embodiments, the particle size of the conductive agent is 5 nm to 50 nm. This allows the conductive agent to be distributed on the primary particles of the first binder and the surface of the positive electrode active material, thereby improving the conductivity of the positive electrode sheet and consequently enabling the secondary battery to achieve both excellent storage performance and low internal resistance. Exemplarily, the particle size of the conductive agent is a value within a range of 5 nm to 10 nm, 5 nm to 20 nm, 5 nm to 30 nm, 5 nm to 40 nm, 5 nm to 50 nm, 10 nm to 20 nm, 10 nm to 30 nm, 10 nm to 40 nm, 10 nm to 50 nm, 20 nm to 30 nm, 20 nm to 40 nm, 20 nm to 50 nm, 30 nm to 40 nm, 30 nm to 50 nm, 40 nm to 50 nm, or any combination thereof.

[0074] In some implementations, the secondary battery includes one or more of the following features:

[0075] (1) In the positive electrode film layer, the mass percentage of the positive electrode active material is 90% to 99%, optionally 95% to 98%, and exemplaryly, the mass percentage of the positive electrode active material is a value within the range of 90%, 93%, 95%, 96%, 98%, 99%, or any two of these; (2) In the positive electrode film layer, the mass percentage of the first binder is 0.5% to 6%, optionally 0.5% to 3%, and exemplaryly, the mass percentage of the first binder is a value within the range of 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, or any two of these; (3) In the positive electrode film layer, the mass percentage of the second binder is 0.1% to 6%, optionally 0.2% to 3%, and exemplaryly, the mass percentage of the second binder is a value between 0.1%, 0.2%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6% or any two of these; (4) In the positive electrode film layer, the mass percentage of the conductive agent is 0.4% to 4%, optionally 0.5% to 2%, and exemplaryly, the mass percentage of the conductive agent is a value between 0.4%, 0.5%, 0.7%, 1%, 2%, 3%, 4% or any two of these.

[0076] In some embodiments, the positive electrode active material includes one or more of lithium-containing transition metal oxides, lithium-containing phosphates, and their respective modified compounds; optionally, the positive electrode active material includes lithium iron phosphate.

[0077] For example, lithium-containing transition metal oxides include lithium cobalt oxides (such as LiCoO2), lithium nickel oxides (such as LiNiO2), lithium manganese oxides (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxides, lithium manganese cobalt oxides, lithium nickel manganese oxides, and lithium nickel cobalt manganese oxides (such as LiNi). 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also known as NCM) 333 LiNi 0.5 Co 0.2 Mn 0.3 O2 (also known as NCM) 523 LiNi 0.5 Co 0.25 Mn 0.25 O2 (also known as NCM) 211 LiNi 0.6 Co 0.2 Mn 0.2 O2 (also known as NCM) 622 LiNi 0.8 Co 0.1 Mn 0.1 O2 (also known as NCM) 811), lithium nickel cobalt aluminum oxide (such as LiNi) 0.85 Co 0.15 Al 0.05 One or more of O2 and its modified compounds.

[0078] For example, lithium-containing phosphates include one or more of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), lithium iron phosphate and carbon composites, lithium manganese phosphate (such as LiMnPO4), lithium manganese phosphate and carbon composites, lithium manganese iron phosphate, and lithium manganese iron phosphate and carbon composites.

[0079] In some embodiments, the specific surface area of ​​the positive electrode active material is 6m². 2 / g~18m 2 / g, optionally, 12m 2 / g~14m 2 / g. Therefore, the positive electrode active material can provide more ion channels, enabling more efficient ion transport and improving the charge / discharge efficiency of the secondary battery. For example, the specific surface area of ​​the positive electrode active material is 6m². 2 / g、8m 2 / g, 10m 2 / g、12m 2 / g、14m 2 / g, 16m 2 / g、18m 2 / g or a range between the values ​​of either / g or any two of them.

[0080] In this application, the specific surface area of ​​the positive electrode active material has a meaning known in the art and can be measured using instruments and methods known in the art. For example, it can be measured using the nitrogen adsorption specific surface area analysis method according to GB / T 19587-2017, and calculated using the BET (Brunauer Emmett Teller) method. The testing instrument can be the Tri-Star 3020 specific surface area and pore size analyzer from Micromeritics, USA.

[0081] In some embodiments, the shear strength of the positive electrode sheet is 0.6 MPa to 1.2 MPa, optionally 0.8 MPa to 1.0 MPa. A shear strength within this range indicates good bonding performance of the positive electrode sheet, which is beneficial for improving the storage performance of the secondary battery. Exemplarily, the shear strength of the positive electrode sheet is a value within the range of 0.6 MPa, 0.7 MPa, 0.8 MPa, 0.9 MPa, 1.0 MPa, 1.1 MPa, 1.2 MPa, or any combination thereof.

[0082] In this application, the shear strength of the positive electrode sheet has a meaning known in the art and can be measured using instruments and methods known in the art. For example, a tensile testing machine can be used. Specifically, a positive electrode sheet sample with a width of 30 mm and a length of 40 mm is cut with a blade. Special double-sided adhesive tape with a width of 20 mm and a length of 50 mm is attached to a steel sheet. The previously cut positive electrode sheet sample is attached to the double-sided adhesive tape with the test surface facing down. Then, a 2 kg pressure roller is used to roll it back and forth three times in the same direction. In addition, special 9 mm × 9 mm double-sided adhesive tape is attached to another steel sheet. The above-mentioned attached positive electrode sheet sample is then bonded together with the 9 mm × 9 mm double-sided adhesive steel sheet. Turn on the power of the tensile testing machine (sensitivity 1N), the indicator light will illuminate. Adjust the limit block to the appropriate position. Fix the end of the steel plate without the electrode attached using the lower clamp, and fix the end of the positive electrode sample without the steel plate attached using the upper clamp. Use the "up" and "down" buttons on the manual controller provided with the tensile testing machine to adjust the position of the upper clamp. Then test at a tensile speed of 10mm / min and read the values. Divide the force that the positive electrode is pulled apart by the area of ​​the 9mm×9mm square attachment as the shear strength of the positive electrode, which characterizes the cohesive strength inside the positive electrode.

[0083] In some embodiments, the film resistance of the positive electrode is 0.01Ω to 0.2Ω, optionally 0.02Ω to 0.1Ω. A film resistance within this range indicates that the positive electrode has low impedance, which is beneficial for reducing the internal resistance of the secondary battery. Exemplarily, the film resistance of the positive electrode is a value within the range of 0.01Ω, 0.02Ω, 0.05Ω, 0.08Ω, 0.1Ω, 0.15Ω, 0.2Ω, or any combination thereof.

[0084] In this application, the film resistance of the positive electrode is a term known in the art and can be measured using instruments and methods known in the art. For example, a film resistance tester can be used for testing. Specifically, the positive electrode is cut into a 10cm × 10cm square, and a film resistance tester (single-point method, test area 153.94mm²) is used. 2 To measure the resistance of the positive electrode membrane, take 4 positive electrode samples for each group, test the resistance of each sample at 10 points, and take the average value as the resistance value of the positive electrode membrane for that group. Then take the average value of the membrane resistance values ​​obtained from each group to obtain the membrane resistance of the positive electrode.

[0085] Methods for preparing secondary batteries

[0086] The second aspect of this application provides a method for preparing a secondary battery, used to prepare the secondary battery described in the first aspect. The method for preparing the secondary battery includes a positive electrode preparation step, which includes a mixing step, comprising pulverizing a first binder raw material, wherein the median particle size of the pulverized first binder raw material is 1 μm to 2 μm, and then stirring the positive electrode active material, the pulverized first binder raw material, and the second binder raw material under stirring conditions of a stirring linear velocity of 5 m / s to 20 m / s and a stirring temperature of -20℃ to 40℃ to obtain a dry-mixed powder containing a positive electrode active material, a first binder, and a second binder raw material. A binder comprises primary particles, wherein the particle size of the positive electrode active material is greater than or equal to the particle size of the primary particles of the first binder, and the particle size of the positive electrode active material is 0.5 μm to 10 μm; a fiberization step includes fiberizing the dry-mixed powder to obtain a fiberized mixed powder containing the positive electrode active material, the first binder, and the second binder, wherein the second binder is fibrous; a tableting step includes calendering the fiberized mixed powder to obtain an electrode film, and then rolling the electrode film with the positive electrode current collector at room temperature to obtain a positive electrode sheet.

[0087] Understandably, in the mixing step, the first binder raw material is pulverized to obtain pulverized first binder raw material, which includes secondary particles formed from the primary particles of the first binder. Through subsequent stirring, the secondary particles in the pulverized first binder raw material can be dispersed into primary particles, and the particle size of the positive electrode active material can be greater than or equal to the particle size of the primary particles of the first binder.

[0088] In this application, by pulverizing, the median particle size of the first binder raw material can be reduced to the aforementioned range. Then, under the aforementioned conditions, stirring is performed to disperse the first binder raw material from secondary particles into primary particles with a particle size less than or equal to that of the positive electrode active material. In this way, the primary particles of the first binder can be distributed on the surface of the small-diameter positive electrode active material. On the one hand, this facilitates the establishment of short-range bonding paths between adjacent positive electrode active material particles by the primary particles of the first binder. On the other hand, this distribution method allows the primary particles of the first binder to contact the positive electrode active material particles relatively uniformly and tightly, thereby forming a relatively continuous and uniform conductive network inside the positive electrode sheet. This allows for efficient electron transport, which helps to reduce the film resistance of the positive electrode sheet. Consequently, the secondary battery can achieve both excellent storage performance and low internal resistance. Meanwhile, the fiberization process enables the second binder raw material to form a fibrous second binder. The fibers can interweave to form a network structure that wraps around the surface of the primary particles of the positive electrode active material and the first binder. In this way, the second binder can establish long-range bonding paths between the positive electrode active materials that are far apart, between the first binders, and between the positive electrode active material and the first binder. This is more conducive to improving the bonding effect of the positive electrode sheet, and thus can further improve the storage performance of the secondary battery.

[0089] Furthermore, since the two binders have the aforementioned positional distribution relationship and are relatively uniformly distributed in the positive electrode film layer, heating is not required during the preparation process, especially during calendering and roll forming processes, to achieve a good bonding effect between the two binders, which helps to reduce energy consumption.

[0090] Understandably, the wet-process electrode technology in related technologies involves a solvent evaporation step. After the solvent evaporates, it leaves more gaps in the positive electrode, reducing the contact area between the first binder and the positive active material, thus lowering the electron transport rate and resulting in a higher internal resistance of the secondary battery. The high-temperature dry-process electrode technology in related technologies requires heating to a certain temperature to soften or melt the binder during the calendering and roll-forming processes to achieve adhesion between the binder and the positive active material. However, at high temperatures, the melted and flowing binder can lead to uneven distribution on the surface of the positive active material, resulting in areas where the binder is too thick or too thin. Areas that are too thick may form a high-resistance insulating layer, while areas that are too thin cannot effectively form a continuous conductive network. Both of these hinder electron transport, further increasing the internal resistance of the secondary battery.

[0091] In some embodiments, the median particle size of the pulverized first binder material is 1 μm to 2 μm. Pulverization reduces the median particle size of the first binder material to this range, facilitating the subsequent dispersion of the first binder material from secondary particles into primary particles with a particle size of 0.1 μm to 0.5 μm during mixing. For example, the median particle size of the pulverized first binder material is a value within the range of 1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2 μm, or any combination thereof.

[0092] In some embodiments, the stirring linear velocity is 5 m / s to 20 m / s. A stirring linear velocity within this range ensures that the frictional heat generated during the mixing of the dry powder mixture is within a suitable range, and also disperses the pulverized first binder raw material into primary particles with a suitable particle size. Exemplarily, the stirring linear velocity is a value within the range of 5 m / s, 6 m / s, 8 m / s, 10 m / s, 12 m / s, 14 m / s, 15 m / s, 16 m / s, 18 m / s, 20 m / s, or any combination thereof.

[0093] In some embodiments, the stirring temperature is -20°C to 40°C, optionally 0°C to 20°C. A stirring temperature within this range can neutralize the heat generated by friction during stirring of the powder, thereby reducing the probability of the first binder raw material melting. This facilitates the first binder maintaining its granular shape and dispersing into primary particles, enabling the secondary battery to achieve both excellent storage performance and low internal resistance. Exemplarily, the stirring temperature is a value within a range of -20°C, -15°C, -10°C, -5°C, 0°C, 2°C, 4°C, 5°C, 6°C, 8°C, 10°C, 12°C, 14°C, 15°C, 16°C, 18°C, 20°C, 22°C, 24°C, 25°C, 26°C, 28°C, 30°C, 32°C, 34°C, 35°C, 36°C, 38°C, 40°C, or any combination thereof.

[0094] In this application, "room temperature" means 25℃±5℃.

[0095] In some embodiments, the fiberization process includes one or more of high-speed shearing, air jet milling, and screw extrusion; optionally, the fiberization process includes high-speed shearing. Using the above methods for fiberization allows the second binder raw material to be fiberized into fibrous form without heating, which helps to further reduce energy consumption.

[0096] In some embodiments, the high-speed shearing process is performed at a shearing rate of 30 m / s to 50 m / s for 5 min to 30 min. Under these conditions, the high-speed shearing process utilizes the frictional heat generated between the dry-mixed powders during the shearing operation to promote the fiberization of the second binder raw material. Therefore, this application can achieve the fiberization process without an additional heating source, which is beneficial for further reducing energy consumption. Exemplarily, the shearing rate is a value within the range of 30 m / s, 35 m / s, 40 m / s, 45 m / s, 50 m / s, or any combination thereof, and the shearing time is a value within the range of 5 min, 10 min, 15 min, 20 min, 25 min, 30 min, or any combination thereof.

[0097] In some embodiments, the calendering pressure is 1 to 10 tons. Calendering under these conditions is beneficial for obtaining electrode films. Exemplarily, the calendering pressure is a value within a range of 1 t, 2 t, 4 t, 6 t, 8 t, 10 t, or any combination thereof.

[0098] In some embodiments, the pressure of the roll forming process is 1t to 20t. Performing the roll forming process under these pressure conditions allows the first binder to plasticize and soften, thereby enabling the positive electrode active material particles to be bonded together and the electrode membrane to be bonded to the positive electrode current collector. Exemplarily, the pressure of the roll forming process is a value within a range of 1t, 3t, 5t, 8t, 10t, 15t, 20t, or any combination thereof.

[0099] In some embodiments, the stirring time is 30 min to 180 min. A stirring time within this range is beneficial for dispersing the pulverized first binder material from secondary particles into primary particles with a particle size of 0.1 μm to 0.5 μm. Exemplarily, the stirring time is a value within a range of 30 min, 60 min, 90 min, 100 min, 120 min, 150 min, 180 min, or any combination thereof.

[0100] In some embodiments, the median particle size of the second binder material is 100 μm to 600 μm. This facilitates the formation of fibrous material with a suitable diameter by fiberization treatment. Exemplarily, the median particle size of the second binder material is a value within a range of 100 μm, 200 μm, 300 μm, 400 μm, 500 μm, 600 μm, or any combination thereof.

[0101] In some embodiments, the median particle size of the first binder raw material is 1 μm to 10 μm, optionally 1 μm to 3 μm. The median particle size of the first binder raw material is within the above range, such that after pulverization and stirring, the first binder raw material can be dispersed into primary particles with a particle size of 0.1 μm to 0.5 μm. Exemplarily, the median particle size of the first binder raw material is a value within a range of 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, or any combination thereof.

[0102] In this application, the term "median particle size" refers to the particle size corresponding to a cumulative particle size distribution percentage of 50%. Physically, it means that 50% of the particles are larger than the median particle size, and 50% are smaller. The median particle size of a material can be determined using methods and instruments known in the art. For example, it can be determined using a laser particle size analyzer (e.g., Malvern Mastersizer 2000E) according to GB / T 19077-2016, Particle Size Distribution Laser Diffraction Method. Specifically, take an appropriate amount of material (ensuring a sample concentration of 8%–12% opacity), add 20 mL of deionized water, and simultaneously sonicate for 5 min (53 kHz / 120 W) to ensure complete dispersion. Then, determine the median particle size D50 of the sample according to GB / T19077-2016 / ISO 13320:2009. Based on the test data, a particle size mass distribution map and a particle size number distribution map are drawn. From the distribution map, it is found that 50% of the particles with a diameter greater than a certain D value account for the total mass, and another 50% of the particles with a diameter less than this D value account for the total mass. This D value is the median particle size of the material.

[0103] In some embodiments, the mass ratio of the pulverized first binder material to the second binder material is (1-15):1, optionally (2-8):1. This ensures that the contents of both the first and second binders in the formed positive electrode film are within suitable ranges. This improves electron transport efficiency and overall conductivity of the positive electrode sheet without affecting the bonding effect, thereby further reducing the film resistance of the positive electrode sheet. This makes it more advantageous for the secondary battery to achieve both excellent storage performance and low internal resistance. For example, the mass ratio of the pulverized first binder material to the second binder material is a value within a range of 1:1, 2:1, 4:1, 6:1, 8:1, 10:1, 12:1, 15:1, or any combination thereof.

[0104] In some embodiments, the dry-mixed powder also includes a conductive agent during the mixing step. This conductive agent further improves the conductivity of the positive electrode, thus helping the secondary battery to achieve both excellent storage performance and low internal resistance.

[0105] In some embodiments, the mass ratio of the positive electrode active material, the pulverized first binder raw material, the second binder raw material, and the conductive agent is (90–99):(0.5–6):(0.1–6):(0.4–4). This allows the secondary battery to achieve both excellent storage performance and low internal resistance.

[0106] In some embodiments, the first binder comprises polyvinylidene fluoride and / or polyvinylidene fluoride-hexafluoropropylene copolymer; alternatively, the first binder comprises polyvinylidene fluoride.

[0107] In some embodiments, the second adhesive includes one or more of polytetrafluoroethylene, ethylene-tetrafluoroethylene copolymer, fluorinated ethylene propylene copolymer, and tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer; optionally, the second adhesive includes polytetrafluoroethylene.

[0108] In some embodiments, the positive electrode active material includes one or more of lithium-containing transition metal oxides, lithium-containing phosphates, and their respective modified compounds; optionally, the positive electrode active material includes lithium iron phosphate.

[0109] In some embodiments, the conductive agent includes conductive carbon particles; alternatively, the conductive agent includes one or more of conductive carbon black, carbon nanotubes, and graphene.

[0110] The term "secondary battery" used in this article refers to a single battery cell, a battery module, or a battery pack. These will be explained separately below.

[0111] Typically, a single secondary battery cell includes a positive electrode, a negative electrode, an electrolyte, and a separator. During charging and discharging, active ions move back and forth between the positive and negative electrodes, inserting and releasing. The electrolyte acts as a conductor between the positive and negative electrodes. The separator, positioned between the positive and negative electrodes, primarily prevents short circuits while allowing ions to pass through.

[0112] Negative electrode sheet

[0113] The negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector, the negative electrode film layer including a negative electrode active material.

[0114] As an example, the negative electrode current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.

[0115] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0116] In some embodiments, the negative electrode active material can be a negative electrode active material known in the art for use in batteries. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, this application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0117] In some embodiments, the negative electrode film layer may optionally include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0118] In some embodiments, the negative electrode film may optionally include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0119] In some embodiments, the negative electrode film may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).

[0120] In some embodiments, the negative electrode sheet can be prepared by dispersing the components used to prepare the negative electrode sheet, such as the negative electrode active material, conductive agent, binder and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto the negative electrode current collector, and then obtaining the negative electrode sheet after drying, cold pressing and other processes.

[0121] Positive electrode sheet

[0122] The positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one surface of the positive current collector, wherein the positive electrode film layer includes the positive electrode active material of this application.

[0123] As an example, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive electrode film layer is disposed on either or both of the opposite surfaces of the positive current collector. In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector can be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0124] During the charging and discharging process of a battery, Li undergoes insertion / extraction and consumption, resulting in varying molar Li content at different discharge states. In the examples of positive electrode active materials in this application, the molar Li content refers to the initial state of the material, i.e., before feeding. When the positive electrode active material is applied to the battery system, the molar Li content changes after charge-discharge cycles.

[0125] In the examples of positive electrode active materials in this application, the molar content of O is only a theoretical value. Oxygen release from the crystal lattice will cause changes in the molar content of oxygen, and the actual molar content of O will fluctuate.

[0126] electrolytes

[0127] The electrolyte acts as a conductor of ions between the positive and negative electrodes. This application does not impose specific restrictions on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, gel, or entirely solid.

[0128] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent.

[0129] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.

[0130] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.

[0131] In some embodiments, the electrolyte may optionally include additives. For example, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc.

[0132] Separating membrane

[0133] In some embodiments, the battery cell also includes a separator. This application does not impose any particular limitation on the type of separator; any known porous separator with good chemical and mechanical stability can be selected.

[0134] In some embodiments, the material of the separator can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0135] In some implementations, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly using a winding or stacking process.

[0136] In some embodiments, the battery cell may include an outer packaging. This outer packaging can be used to encapsulate the electrode assembly and electrolyte described above.

[0137] In some embodiments, the outer packaging of the battery cell can be a rigid shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of the battery cell can also be a flexible package, such as a pouch. The material of the flexible package can be plastic; examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0138] This application does not impose any particular limitation on the shape of the battery cell; it can be cylindrical, square, or any other arbitrary shape. For example, Figure 2 The example shown is a square-structured battery cell 5.

[0139] In some implementations, refer to Figure 3The outer packaging may include a housing 51 and a top cover assembly 53. The housing 51 may include a base plate and side plates connected to the base plate, the base plate and side plates forming a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the top cover assembly 53 can cover the opening to close the receiving cavity. A positive electrode sheet, a negative electrode sheet, and a separator can be formed into an electrode assembly 52 through a winding process or a stacking process. The electrode assembly 52 is encapsulated within the receiving cavity. Electrolyte is immersed in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in a single battery cell 5 can be one or more, which can be selected by those skilled in the art according to specific practical needs.

[0140] In some implementations, individual battery cells can be assembled into a battery module. The number of individual battery cells contained in a battery module can be one or more, and the specific number can be selected by those skilled in the art based on the application and capacity of the battery module.

[0141] Figure 4 This is battery module 4, used as an example. (See reference...) Figure 4 In battery module 4, multiple battery cells 5 can be arranged sequentially along the length of battery module 4. Of course, they can also be arranged in any other manner. Furthermore, these multiple battery cells 5 can be fixed in place using fasteners.

[0142] Optionally, the battery module 4 may also include a housing with a receiving space in which multiple battery cells 5 are received.

[0143] In some embodiments, the battery modules described above can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be one or more, the specific number of which can be selected by those skilled in the art according to the application and capacity of the battery pack.

[0144] Figure 5 and Figure 6 This is battery pack 1 as an example. (See reference...) Figure 5 and Figure 6 The battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box includes an upper body 2 and a lower body 3, with the upper body 2 covering the lower body 3 to form a closed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.

[0145] Electrical appliances

[0146] A third aspect of this application provides an electrical device that includes a secondary battery provided in the first aspect of this application, or a secondary battery prepared according to the preparation method of the second aspect of this application.

[0147] Secondary batteries can be used as a power source for electrical devices or as an energy storage unit for electrical devices. Electrical devices can include, but are not limited to, mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0148] As an electrical device, you can choose individual battery cells, battery modules, or battery packs according to your usage requirements.

[0149] Figure 7 This is an example of an electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery for this device, a battery pack or battery module can be used.

[0150] Another example device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use a single battery cell as their power source.

[0151] Example

[0152] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0153] Example 1

[0154] Preparation of secondary batteries:

[0155] (1) Preparation of positive electrode sheet

[0156] a. Mixing Step: The first binder raw material, polyvinylidene fluoride (PVDF), is subjected to air jet milling. The median particle size of the milled first binder raw material is 1.4 μm. Then, the positive electrode active material, lithium iron phosphate, the milled first binder raw material, the second binder raw material, polytetrafluoroethylene (PTFE), and the conductive agent, conductive carbon black, are added to a high-speed mixer at a mass ratio of 96:2:0.8:1.2. The mixture is stirred at a stirring linear velocity of 12 m / s, a stirring time of 90 min, and a stirring temperature of 20 °C to obtain a dry-mixed powder. The median particle size of the first binder raw material is 5 μm, the median particle size of the second binder raw material is 450 μm, the number average molecular weight of the first binder is 750,000, the mass ratio of the milled first binder raw material to the second binder raw material is 2.5:1, the particle size of the positive electrode active material is 1 μm to 4 μm, and the particle size of the conductive agent is 30 μm to 50 μm.

[0157] b. Fiberization step: Set the shearing speed to 40m / s and the shearing time to 15min, and perform fiberization treatment on the dry mixed powder through a high-speed mixer to obtain a fiberized mixed powder, wherein the second binder PTFE is fibrous and the average diameter of the fiber is 25nm.

[0158] c. Tableting step: Set the pressure of the roller press to 2t, and use the roller press to calender the fibrous mixed powder to obtain the positive electrode film. Then set the pressure of the counter roller press to 6t, and use the counter roller press to laminate the positive electrode film onto the positive electrode current collector aluminum foil at 25℃ to obtain the positive electrode sheet.

[0159] Characterization of the positive electrode sheet:

[0160] (a) Shear strength test

[0161] Cut a positive electrode sample with a width of 30mm and a length of 40mm using a blade. Apply special double-sided tape (20mm wide and 50mm long) to a steel sheet. Place the previously cut positive electrode sample onto the double-sided tape, test side down. Then, use a 2kg pressure roller to roll back and forth three times in the same direction. Separately, apply special 9mm×9mm double-sided tape to another steel sheet. Attach the previously prepared positive electrode sample to the 9mm×9mm double-sided tape steel sheet. (Think twice before opening.) Power on the tensile testing machine (sensitivity 1N), indicator light illuminates. Adjust the limit block to the appropriate position. Fix the end of the steel plate without the electrode attached using the lower clamp, and fix the end of the positive electrode sample without the steel plate attached using the upper clamp. Use the "up" and "down" buttons on the manual controller provided with the tensile testing machine to adjust the position of the upper clamp. Then, test at a tensile speed of 10 mm / min and read the value. Divide the force that the positive electrode is pulled apart by the area of ​​the 9 mm × 9 mm square attachment to obtain the shear strength of the positive electrode. In Example 1, the shear strength of the positive electrode is 0.86 MPa.

[0162] (b) Scanning electron microscopy (SEM) testing

[0163] The microstructure of the positive electrode was obtained by SEM testing.

[0164] Figure 8 This is a scanning electron microscope image of the positive electrode in Example 1. Figure 9 yes Figure 8 A partial magnified view of the scanning electron microscope image of the positive electrode in Example 1 shown, as follows: Figure 8 and Figure 9 As shown, the first binder is in the form of a single particle (i.e., a primary particle), and the primary particles of the first binder are distributed on the surface of the positive electrode active material. The second binder is fibrous, and the second binder is wrapped around the surface of the positive electrode active material and the primary particles of the first binder. The conductive agent is distributed on the surface of the positive electrode active material and the primary particles of the first binder.

[0165] (c) Particle size testing

[0166] Peel the positive electrode film from the positive electrode current collector, fix the peeled positive electrode film onto the sample stage, install the sample stage into the sample holder and lock it in place, turn on the power of the argon ion cross-section polisher (JEOL IB-09010CP argon ion cross-section polisher from Japan) and perform vacuuming (10 -7Argon flow rate was set to 0.12 MPa and polishing time to 90 min. The sample stage was adjusted to swing mode to begin polishing. Polishing was performed at different angles to obtain cross-sections of the positive electrode film at five different angles. Scanning electron microscopy was used to observe the cross-sections at the five different angles. A test sample with a length × width of 50 mm × 100 mm was randomly selected from the cross-section at each angle. Five test areas were randomly selected from the test sample, and the particle size of the positive electrode active material particles, the primary particles of the first binder, and the conductive agent in each test area was read at 1000x magnification (i.e., the distance between the two farthest points on the particle was taken as the particle size of the material to be tested). The particle size range of the particles to be tested at that angle was obtained. The particle size of the particles to be tested at the five different angles was then tested to obtain the particle size range of the particles to be tested. In Example 1, the particle size D1 of the positive electrode active material is 1 μm to 4 μm, the particle size D2 of the primary particles of the first binder is 0.16 μm to 0.19 μm, and the particle size D3 of the conductive agent is 30 μm to 50 μm.

[0167] (d) Diaphragm resistance test

[0168] The positive electrode was cut into a 10cm x 10cm square and tested using a film resistance meter (single-point method, test area 153.94mm²). 2 The resistance of the positive electrode membrane was measured. Four positive electrode samples were taken from each group, and the resistance values ​​of each sample were measured at 10 points. The average value was taken as the resistance value of the positive electrode membrane in that group. The average value of the membrane resistance values ​​obtained from each group was then taken to obtain the membrane resistance of the positive electrode. In Example 1, the membrane resistance of the positive electrode was 0.0498Ω.

[0169] (2) Preparation of negative electrode sheet

[0170] The negative electrode material graphite, the binder styrene-polybutadiene rubber, the conductive agent conductive carbon black, and the thickener sodium carboxymethyl cellulose are thoroughly mixed in an appropriate amount of deionized water at a weight ratio of 96:1.8:0.8:1.4 to form a negative electrode slurry. The negative electrode slurry is coated onto the negative electrode current collector copper foil to form a negative electrode film layer. After drying and cold pressing, the negative electrode sheet is obtained.

[0171] (3) Preparation of electrolyte

[0172] Ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), and ethylene carbonate (EC) were mixed in a volume ratio of 3:2:6 to form an organic solvent. LiPF6 was then dissolved in the organic solvent to obtain an electrolyte with a LiPF6 concentration of 1 mol / L.

[0173] (4) Separating membrane:

[0174] Polyolefin material is used as the separator, and the separator thickness is 18μm.

[0175] (5) Preparation of secondary batteries:

[0176] The positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes to provide insulation. The electrode assembly is then formed by bending and winding. The electrode assembly is placed in outer packaging, dried, and then injected with the prepared electrolyte. After vacuum sealing, settling, formation, and shaping, a secondary battery is obtained.

[0177] Secondary battery performance test:

[0178] (1) High-temperature storage performance test

[0179] At 25°C, the prepared secondary battery was charged to 3.65V with a constant current of 0.33C, then charged to 0.05C with a constant voltage, and then discharged to 2.5V with a constant current of 0.33C. The measured capacity was recorded as C0.

[0180] The secondary battery was charged at a constant current of 0.33C to 3.65V, and then charged at a constant voltage to a current of 0.05C to reach full charge. The fully charged secondary battery was placed in a 60℃ constant temperature oven. Every 30 days, the battery was taken out and discharged at 25℃ at a constant current of 0.33C to 2.5V, and then discharged at a constant voltage to a current of 0.05C. The capacity was measured as Cn, and the capacity retention rate (%) was calculated as Cn / C0. The capacity retention rate after 60 days at 60℃ was recorded. The test results are shown in Table 2 below.

[0181] (2) DC internal resistance (DCR) test

[0182] At 25℃, the prepared secondary battery was charged at a constant current of 0.33C to a cutoff voltage of 3.65V, and then charged at a constant voltage of 3.65V to a current of 0.05C, at which point the secondary battery was fully charged. After the fully charged secondary battery was left to stand for 5 minutes, it was discharged at a current of 0.33C to a state of charge of 50% and the voltage V1 was recorded. Then it was discharged at a current of 2C for 30 seconds and the voltage V2 was recorded. The internal resistance of the battery during charging and discharging was calculated as DCR = (V2 - V1) / current. The test results are recorded in Table 2 below.

[0183] Example 2

[0184] The secondary battery was prepared using the same method as in Example 1, except that in the mixing step of preparing the positive electrode sheet, the median particle size of the pulverized first binder raw material was 1 μm, and the stirring conditions were: stirring linear speed of 20 m / s, stirring time of 75 min, and stirring temperature of 10 °C, to obtain dry mixed powder.

[0185] Example 3

[0186] The secondary battery was prepared using the same method as in Example 1, except that in the mixing step of preparing the positive electrode sheet, the median particle size of the pulverized first binder raw material was 2 μm, and the stirring conditions were: stirring linear speed of 5 m / s, stirring time of 120 min, and stirring temperature of 24 °C, to obtain dry mixed powder.

[0187] Example 4

[0188] The secondary battery was prepared using the same method as in Example 1, except that in the mixing step of preparing the positive electrode sheet, the median particle size of the pulverized first binder raw material was 1.6 μm, and the stirring conditions were: stirring linear speed of 14 m / s, stirring time of 90 min, and stirring temperature of 22 °C, to obtain dry mixed powder.

[0189] Comparative Example 1

[0190] The secondary battery was prepared using the same method as in Example 1, except that the pressing step in the preparation of the positive electrode sheet included: adding the fibrous mixed powder to the solvent N-methylpyrrolidone, stirring evenly to form a positive electrode slurry, coating the positive electrode slurry onto the positive electrode current collector aluminum foil to form a positive electrode film layer, and then drying and cold pressing to obtain the positive electrode sheet.

[0191] Comparative Example 2

[0192] The secondary battery was prepared using the same method as in Example 1, except that the positive electrode sheet only included the first binder PVDF and did not include the second binder PTFE.

[0193] Comparative Example 3

[0194] The secondary battery was prepared using the same method as in Example 1, except that the positive electrode sheet only included the second binder PTFE and did not include the first binder PVDF.

[0195] Comparative Example 4

[0196] The secondary battery was prepared using the same method as in Example 1, except that the median particle size of the first binder material was 10 μm. Then, instead of air-jet milling the first binder material, the positive electrode active material lithium iron phosphate, the first binder material polyvinylidene fluoride (PVDF), the second binder material polytetrafluoroethylene (PTFE), and the conductive agent conductive carbon black were directly stirred and mixed in the same manner as in Example 1 to obtain a dry powder. In the dry powder mixture, the first binder was not dispersed into primary particles, and the particle size of the first binder was 5 μm to 13 μm. Please refer to Table 1 below for details.

[0197] Comparative Example 5

[0198] The secondary battery was prepared using the same method as in Example 1, except that the preparation process of the positive electrode included: a) a mixing step: lithium iron phosphate, the first binder material polyvinylidene fluoride (PVDF), the second binder material polytetrafluoroethylene (PTFE), and the conductive agent conductive carbon black were added to a high-speed mixer in a mass ratio of 96:2:0.8:1.2 and stirred to obtain a dry-mixed powder; wherein the median particle size of the first binder material was 5 μm, the median particle size of the second binder material was 450 μm, and the number average molecular weight of the first binder was 750,000;

[0199] b. Fiberization step: Set the shearing speed to 40m / s and the shearing time to 15min, and perform fiberization treatment on the dry mixed powder through a high-speed mixer to obtain a fiberized mixed powder, wherein the second binder PTFE is fibrous and the average diameter of the fiber is 25nm.

[0200] c. Tableting step: Set the pressure of the roller press to 2t and the temperature to 160℃. Use the roller press to calender the fibrous mixed powder to obtain the positive electrode film. Then set the pressure of the counter-roller to 6t and the temperature to 160℃. Use the counter-roller to laminate the positive electrode film onto the positive electrode current collector aluminum foil to obtain the positive electrode sheet.

[0201] The positive electrode sheets prepared in Examples 2 to 4 and Comparative Examples 1 to 5 were characterized using the same test methods as in Example 1, and the performance of the secondary batteries prepared in Examples 2 to 4 and Comparative Examples 1 to 5 was tested.

[0202] Table 1 below shows the relevant parameters of the positive electrode sheets in Examples 1 to 4 and Comparative Examples 1 to 5. Table 2 below shows the shear strength and film resistance of the positive electrode sheets prepared in Examples 1 to 4 and Comparative Examples 1 to 5, as well as the performance test results of the prepared secondary batteries.

[0203] Table 1

[0204]

[0205] In Table 1, " / " indicates that the symbol does not exist.

[0206] Table 2

[0207]

[0208] In Table 2, " / " indicates that the symbol does not exist.

[0209] As can be seen from Tables 1 and 2, Examples 1 to 4 disperse the first binder into primary particles with a particle size within the above range, so that the particle size of the positive electrode active material is greater than or equal to the particle size of the primary particles of the first binder. This allows the primary particles of the first binder to be distributed on at least a portion of the surface of the positive electrode active material, and the prepared secondary battery can achieve both excellent storage performance and low internal resistance.

[0210] Comparative Example 1 uses a wet process to prepare the positive electrode sheet, which dissolves the first binder in the slurry. Therefore, there are no primary particles of the first binder in the positive electrode sheet. The shear strength of the prepared positive electrode sheet is comparable to that of the positive electrode sheets prepared in Examples 1 to 4. However, the film resistance of the positive electrode sheet is significantly increased, resulting in a significant increase in the internal resistance of the secondary battery.

[0211] In Comparative Example 2, the positive electrode sheet only includes the first binder PVDF, which makes it impossible to form the positive electrode sheet during preparation.

[0212] In Comparative Example 3, the positive electrode sheet only includes the second binder PTFE, which reduces the shear strength of the positive electrode sheet and increases the film resistance, affecting the storage performance and internal resistance of the secondary battery.

[0213] In Comparative Example 4, the particle size of the positive electrode active material is smaller than that of the first binder, causing the positive electrode active material to be distributed on the surface of the first binder, which significantly reduces the shear strength of the positive electrode sheet and thus significantly reduces the storage performance of the secondary battery.

[0214] Comparative Example 5 uses a high-temperature dry process to prepare the positive electrode sheet, which prevents the first binder from melting and forming primary particles. The shear strength of the prepared positive electrode sheet is comparable to that of the positive electrode sheets prepared in Examples 1 to 4, but the film resistance of the positive electrode sheet is significantly increased, resulting in a significant increase in the internal resistance of the secondary battery.

[0215] Examples 5 to 8

[0216] The secondary battery was prepared using the same method as in Example 1, except that the mass ratio of the pulverized first binder material and the second binder material was changed in the mixing step of the positive electrode preparation. Please refer to Table 3 below for details. The positive electrode sheets prepared in Examples 5 to 8 were characterized using the same test methods as in Example 1, and the performance of the secondary batteries prepared in Examples 5 to 8 was tested.

[0217] Table 3 below shows the relevant parameters of the positive electrode sheets in Examples 5 to 8, and Table 4 below shows the shear strength and film resistance of the positive electrode sheets prepared in Examples 5 to 8, as well as the performance test results of the prepared secondary batteries.

[0218] Table 3

[0219]

[0220]

[0221] Table 4

[0222]

[0223] As can be seen from Tables 3 and 4, by controlling the mass ratio of the first binder to the second binder to (1-15):1, the secondary batteries prepared in Examples 5 to 8 can achieve both excellent storage performance and low internal resistance.

[0224] Example 9

[0225] The secondary battery was prepared using the same method as in Example 1, except that the type of the first binder was different. Please refer to Table 5 below for details.

[0226] The positive electrode sheet prepared in Example 9 was characterized using the same test method as in Example 1, and the performance of the secondary battery prepared in Example 9 was tested.

[0227] Table 5 below shows the relevant parameters of the positive electrode sheet in Example 9, and Table 6 below shows the shear strength and film resistance of the positive electrode sheet prepared in Example 9, as well as the performance test results of the prepared secondary battery. In addition, for ease of comparison, the relevant parameters in Example 1 are also shown here.

[0228] Table 5

[0229]

[0230] Table 6

[0231]

[0232] As can be seen from Tables 5 and 6, the secondary batteries prepared in Examples 1 and 9 by adding the above-mentioned type of first binder to the positive electrode sheet can achieve both excellent storage performance and low internal resistance.

[0233] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A secondary battery, characterized in that, The device includes a positive electrode sheet, which includes a positive current collector and a positive electrode film layer located on at least one side of the positive current collector. The positive electrode film layer includes a positive active material, a first binder, and a second binder. The first binder includes primary particles, and the second binder is fibrous. The particle size of the positive electrode active material is greater than or equal to the particle size of the primary particles of the first binder, and the particle size of the positive electrode active material is 0.5 μm to 10 μm; The primary particles of the first binder are distributed on at least a portion of the surface of the positive electrode active material.

2. The secondary battery according to claim 1, characterized in that, The particle size of the positive electrode active material is 0.5 μm to 5 μm; and / or, The primary particles of the first adhesive have a particle size of 0.1 μm to 0.5 μm.

3. The secondary battery according to claim 1 or 2, characterized in that, The particle size of the positive electrode active material is 1 μm to 4 μm; and / or, The primary particles of the first adhesive have a particle size of 0.15 μm to 0.2 μm.

4. The secondary battery according to any one of claims 1 to 3, characterized in that, In the positive electrode film layer, the mass ratio of the first binder to the second binder is (1-15):

1.

5. The secondary battery according to any one of claims 1 to 4, characterized in that, In the positive electrode film layer, the mass ratio of the first binder to the second binder is (2-8):

1.

6. The secondary battery according to any one of claims 1 to 5, characterized in that, The second adhesive includes a fiberizable adhesive.

7. The secondary battery according to any one of claims 1 to 6, characterized in that, The first adhesive comprises polyvinylidene fluoride and / or polyvinylidene fluoride-hexafluoropropylene copolymer.

8. The secondary battery according to claim 7, characterized in that, The number average molecular weight of the first adhesive is 200,000 to 2,000,000.

9. The secondary battery according to any one of claims 1 to 8, characterized in that, The positive electrode film layer also includes a conductive agent, the particle size of which is smaller than the particle size of the primary particles of the first binder.

10. The secondary battery according to claim 9, characterized in that, The conductive agent has a particle size of 5nm to 50nm.

11. The secondary battery according to claim 9 or 10, characterized in that, Includes one or more of the following features: (1) In the positive electrode film layer, the mass percentage of the positive electrode active material is 90% to 99%; (2) In the positive electrode film layer, the mass percentage of the first binder is 0.5% to 6%; (3) In the positive electrode film layer, the mass percentage of the second binder is 0.1% to 6%; (4) In the positive electrode film layer, the mass percentage of the conductive agent is 0.4% to 4%.

12. The secondary battery according to any one of claims 1 to 11, characterized in that, The positive electrode active material includes one or more of lithium-containing transition metal oxides, lithium-containing phosphates, and their respective modified compounds.

13. The secondary battery according to any one of claims 1 to 12, characterized in that, The positive electrode active material includes lithium iron phosphate.

14. The secondary battery according to any one of claims 1 to 13, characterized in that, The shear strength of the positive electrode sheet is 0.6 MPa to 1.2 MPa.

15. The secondary battery according to any one of claims 1 to 14, characterized in that, The film resistance of the positive electrode is 0.01Ω to 0.2Ω.

16. A method for preparing a secondary battery, characterized in that, This includes the preparation of a positive electrode sheet, wherein the preparation steps of the positive electrode sheet include: The mixing step includes pulverizing the first binder raw material, wherein the median particle size of the pulverized first binder raw material is 1μm to 2μm, and then stirring the positive electrode active material, the pulverized first binder raw material, and the second binder raw material under the conditions of stirring linear velocity of 5m / s to 20m / s and stirring temperature of -20℃ to 40℃ to obtain a dry-mixed powder containing the positive electrode active material, the first binder, and the second binder raw material. The first binder includes primary particles, and the particle size of the positive electrode active material is greater than or equal to the particle size of the primary particles of the first binder, wherein the particle size of the positive electrode active material is 0.5μm to 10μm. The fiberization step includes fiberizing the dry-mixed powder to obtain a fiberized mixed powder containing the positive electrode active material, the first binder, and the second binder, wherein the second binder is fibrous. The tableting step includes calendering the fibrous mixed powder to obtain an electrode film, and then rolling the electrode film with a positive current collector at room temperature to obtain a positive electrode sheet.

17. The preparation method according to claim 16, characterized in that, The fiberization process includes one or more of the following: high-speed shearing, air jet milling, and screw extrusion.

18. The preparation method according to claim 17, characterized in that, The high-speed shearing process is carried out at a shearing speed of 30 m / s to 50 m / s for 5 min to 30 min.

19. The preparation method according to any one of claims 16 to 18, characterized in that, Includes one or more of the following features: (1) The pressure of the calendering process is 1t to 10t; (2) The pressure of the roller pressing composite treatment is 1t to 20t; (3) The stirring time for the stirring treatment is 30 min to 180 min; (4) The median particle size of the second binder raw material is 100μm to 600μm; (5) The median particle size of the first binder raw material is 1 μm to 10 μm; (6) The mass ratio of the first binder raw material after crushing to the second binder raw material is (1-15):

1.

20. The preparation method according to any one of claims 16 to 19, characterized in that, In the mixing step, the dry-mixed powder also includes a conductive agent.

21. The preparation method according to claim 20, characterized in that, The mass ratio of the positive electrode active material, the pulverized first binder raw material, the second binder raw material and the conductive agent is (90-99):(0.5-6):(0.1-6):(0.4-4).

22. An electrical appliance, characterized in that, It includes the secondary battery according to any one of claims 1 to 15, or the secondary battery prepared by the preparation method according to any one of claims 16 to 21.